A Qualitative Study of EFL Students’ Experiences with AI Tools in English Language Learning - Yunita Winata; Weningtyas Parama Iswari; Susilo Susilo; Effendi Limbong (Cetta: Jurnal Ilmu Pendidikan, 2026)
The development of artificial intelligence (AI) technology has provided new opportunities in learning English as a foreign language (EFL), particularly in helping students develop vocabulary, academic writing skills, and self-confidence in independent learning. This study aims to explore the experiences of EFL students at Mulawarman University in using AI-based tools, such as ChatGPT, Grammarly, and Copilot, to support English learning. This study used a qualitative approach involving students in semesters 2 through 6 as participants. Data were collected through questionnaires completed by 40 students and in-depth interviews with several informants selected based on their questionnaire responses. The data were analyzed using thematic analysis to identify students' motivations, benefits, challenges, and adaptation strategies in using AI. The results showed that ChatGPT and Grammarly were the most dominant AI tools used because they provided immediate feedback, helped develop ideas, improved sentence structure, and supported vocabulary and writing skills. The use of AI also helped increase students' confidence in understanding and producing English. However, this study identified challenges such as potential dependency, a lack of guidance on technology use, and the need for digital literacy to critically evaluate AI output. This study concludes that the use of AI in EFL learning has great potential if supported by lecturer guidance, strengthening digital literacy, and adaptive usage strategies.